A STUDY OF ERROR ON ENGLISH SPEECH USED BY THE RADIO ANNOUNCER AT BRASS FM KEDIRI - Rino Sardanto (OKARA: Jurnal Bahasa dan Sastra, 2014)
Error is violation from the rule of English grammar. The purpose of this study is to describe the kinds of errors and to calculate the frequency of occurrences of the types of errors made by the announcer at Brass FM Kediri. The data in this study were obtained from the English conversation program at Brass FM Kediri. The data was collected by doing 2 week observation to investigate the process of English conversation between announcer and participants of Brass FM in English Corner program. The researcher used the recording to know the errors of English speaking made by the announcer. The errors found were analyzed using Surface Strategy Taxonomy from Dulay (1982) and were classified into errors of omission, errors of addition, errors of misformation, and errors of disordering. Based on the analysis, it is show that highest frequency of occurrence of the types of errors is misformation with the percentage 47.92 %, omission with the percentage 33.33 % then followed by addition with the percentage of 16.67%, and the last percentage disordering 2.08%. From the data above that the announcer still makes errors in using grammar especially in the use of plural –s/-es, pronoun and to be. Based on the result of the study, it can be concluded that the announcer of radio Brass FM in English Corner still has many problems in using grammar in conversation on English broadcast. It suggests that the language learner must study more about English grammar and not forget to pay attention the punctuation, conjunction, preposition and any kinds of tenses to make of English grammar mastery.